Respuesta :

9514 1404 393

Answer:

  -36

Step-by-step explanation:

Using the expression for the general term, you can fill in the known values and solve for the parameters of the sequence.

  an = a1 +d(n -1)

  a8 = a1 + d(8 -1) = 60

  a12 = a1 + d(12 -1) = 48

The difference of these equations is ...

  (a1 +7d) -(a1 +11d) = (60) -(48)

  -4d = 12

  d = -3

Substituting into the first equation, we have ...

  a1 +7(-3) = 60

  a1 = 81 . . . . . . . . . add 21

Then the 40th term is ...

  a40 = 81 -3(40 -1) = 81 -117

  a40 = -36

ACCESS MORE